2017
DOI: 10.3892/etm.2017.4549
|View full text |Cite
|
Sign up to set email alerts
|

Biliverdin administration ameliorates cerebral ischemia reperfusion injury in rats and is associated with proinflammatory factor downregulation

Abstract: Biliverdin (BV), one of the heme oxygenase-1 (HO-1) catalytic products, has been demonstrated to have protective effects in liver ischemia reperfusion injury (IRI). The present study aimed to explore the effects of BV on cerebral IRI, and to investigate the potential mechanisms thereof. Adult male SD rats, weighing 200–240 g, were randomly divided into sham (group S), cerebral ischemia reperfusion control (group C) and BV (group BV) groups. Rats in group C underwent transient middle cerebral artery occlusion (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…In a further study, intravenously applied PEGylated COHb in a transient focal cerebral ischemia model in rats resulted in reduced infarct volumes and better neurologic deficit scores [49]. Besides CO, biliverdin treatment has also been shown to ameliorate oxidative injury on neurons and decrease infarct size in rat MCAO models [50, 51].…”
Section: The Ho-1 Pathway and Ischemic Stroke: Preclinical Resultsmentioning
confidence: 99%
“…In a further study, intravenously applied PEGylated COHb in a transient focal cerebral ischemia model in rats resulted in reduced infarct volumes and better neurologic deficit scores [49]. Besides CO, biliverdin treatment has also been shown to ameliorate oxidative injury on neurons and decrease infarct size in rat MCAO models [50, 51].…”
Section: The Ho-1 Pathway and Ischemic Stroke: Preclinical Resultsmentioning
confidence: 99%
“…Our previous research indicated that bilirubin possesses a power anti-inflammatory property, which showed significant cytoprotective effects against oxidative and inflammatory damage in multiple cell lines 40 , 63 - 65 . Biliverdin, as a precursor substance of bilirubin, has also been demonstrated as an important cytoprotective and anti-inflammatory molecule 34 , 35 . Then, we further used immunostaining to evaluate the level of pro-inflammatory cytokines, including IL-1 and TNF-α, which play an essential role in wound repair (Figure 8 A-B).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Xing et al reported that biliverdin nanoagent could effectively elevate tumor temperature under mild NIR irradiation, and consequently induce efficient photothermal tumor ablation 4 . In addition, biliverdin also showed a cytoprotective effect by the antioxidative and anti-inflammatory properties 32 - 34 , which would be beneficial for wound healing. Based on these facts, biliverdin holds the potential to be utilized as not only a biodegradable photothermal agent for PTT but also a bioactive drug for the following wound healing, rather than PTT waste.…”
Section: Introductionmentioning
confidence: 99%
“…The YPs: Aβ, amyloid β; BV, biliverdin; BVR, biliverdin reductase; CO, carbon monoxide; CREB, cAMP-responsive element-binding; HMOX, heme oxygenase; NFT, neurofibrillary tangles; Nrf2, nuclear factor erythroid 2–related factor 2; NF-κB, nuclear factor kappa-light-chain-enhancer of activated B cells; NO, nitric oxide; ROS, reactive oxygen species; RNS, reactive nitrogen species; UCB, unconjugated bilirubin; UPR, unfolded protein response; UPS, ubiquitin-proteasome system; Tp53, human p53 tumor protein. (For details see [ 201 , 202 , 203 , 204 , 205 , 206 , 207 ]).…”
Section: The Yellow Players (Yp)mentioning
confidence: 99%